Applications and prospects of different functional hydrogels in meniscus repair - Jin, Pan; Liu, Lei; Chen, Xichi; Cheng, Lin; Zhang, Weining; Zhong, Gang (Frontiers in Bioengineering and Biotechnology, 2022)
The meniscus is a kind of fibrocartilage plate that serves as a cushion in the knee joint to alleviate the mechanical load. It is commonly injured, but it cannot heal spontaneously. Traditional meniscectomy is not currently recommended as this treatment tends to cause osteoarthritis. Due to their good biocompatibility and versatile regulation, hydrogels are emerging biomaterials in tissue engineering. Hydrogels are excellent candidates in meniscus rehabilitation and regeneration because they are fine-tunable, easily modified, and capable of delivering exogenous drugs, cells, proteins, and cytokines. Various hydrogels have been reported to work well in meniscus-damaged animals, but few hydrogels are effective in the clinic, indicating that hydrogels possess many overlooked problems. In this review, we summarize the applications and problems of hydrogels in extrinsic substance delivery, meniscus rehabilitation, and meniscus regeneration. This study will provide theoretical guidance for new therapeutic strategies for meniscus repair.